Parental intervention strategies and operating mechanism on adolescent social media use—The concept of literacy improvement based on interaction - Wang, Bowei; Chen, Jiali (Frontiers in Psychology, 2022)
This study focuses on a realistic picture of parental intervention in the use of social media among teenagers in the post-pandemic era. First, based on a questionnaire survey and in-depth interviews, and under the guidance of the concept of interactive literacy improvement, we propose a conceptual model and a verifiable measurement dimension of parental-mediated intervention. Second, based on the comparison of parent–child samples, it was found that parental-mediated intervention strategies are often used in families, and parents and children have roughly the same cognition and preference for the four intervention strategies. However, parents reported that they use intervention strategies much more frequently than perceived by their children. Third, we constructed and verified the prediction model of “individual technical characteristics-online family environment-parental-mediated intervention,” namely, the hierarchical progressive logic of parental-mediated intervention, and realized the systematization of influencing factors. The study confirmed that the effectiveness of parental-mediated intervention is improved by parent–children “cohesion.” In the follow-up, we will focus on the new perspective of theoretical research on parental intervention and intra-generational digital inequality among adolescents.